(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2023)
The article updates the study of gastronyms as markers of identity in contemporary French-language literary discourse. The author analyses the novels of contemporary French-language authors, in particular Muriel Barbery, Amélie Notomb, Michel Houellebecq, with a retrospective to the French literature of realism, naturalism, regionalism, and mentions the novels of Émile Zola, Boris Vian, and Marcel Pagnol in this regard. In the contemporary French-language literary discourse, gastronyms are additional means of characterising characters (primarily for a more complete disclosure of their psychological portrait, a means of representing them as representatives of a particular social stratum or ethnic group). Often, culinary discourse becomes an ethnographic marker, a gastronomic guide to a particular area. Muriel Barbery’s novels “Delicacies”, Amélie Notomb’s “Neither Eve nor Adam”, and Michel Houellebecq’s “Submission” catechise regional, national, and international culinary traditions that are organically combined in the French culinary preferences. The love of eating French regional dishes becomes a local characteristic of the characters, describing them as typical representatives of a certain area, a certain region, and identifying their family affiliation, as regional cuisine is associated primarily with home cooking. The characters’ fascination with national, “haute” cuisine represents them as representatives of the French nation, as people who are proud of their country and its gastronomic culture, and identifies them as active, conscious citizens. The tendency to consume international gastronomic items characterises the characters as atypical representatives of their nation, identifies them as cosmopolitans, people who break away from their origins, are open to the world, to everything new. Sometimes the gastronomic preferences of the characters destroy social, national, and cultural stereotypes, which is vividly represented in the novels The “Elegance of the Hedgehog” by Muriel Barbery and “Neither Eve nor Adam” by Amelie Notomb, whose main characters deliberately break the generally accepted rules.